Possible classification of the methods of operational research applicable in the field of defense - Mučibabić, S. (Yugoslav Journal of Operations Research; Vol 16 No 2 (2006): Vol. 16 No. 2, 2016)
The overall dynamic development of operational research in various fields of human activities urges the need for a clearer and mathematically more explicit classification of its methods. This need is also very urgent in the field of defense, particularly because of the complications of modern conflicts, as well as of new security requirements. One of the possible classifications of methods based on the theory of games as a mathematical model for solving conflict situations is presented in this paper. The connections between methods and their mathematical description are underlined.